2012
DOI: 10.1080/13803395.2012.683856
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional effects of acculturation on English-language neuropsychological test performance among HIV+ Caribbean Latinas/os

Abstract: Acculturation has been linked to neuropsychological performance in several ethnic groups. However, research among Latina/o samples has examined primarily Mexican/Mexican Americans, and has not examined Latina/o clinical populations of Caribbean descent. This study examined associations between a multidimensional acculturation measure and neuropsychological performance among 82 HIV+ Caribbean Latina/o adults. Multivariate results showed that U.S. acculturation significantly predicted 11–14% of the variance in G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 33 publications
1
40
0
Order By: Relevance
“…This finding is supported unambiguously by Coffey and colleagues' research, which demonstrated that more highly acculturated individuals, as measured by a language-based acculturation measure, exhibited better performance on the WCST total trials and non-perseverative errors relative to a those less acculturated (Coffey et al, 2005). Beyond this circumscribed finding, linguistic cultural factors have also been found to have a significant effect on an array of both verbal and nonverbal cognitive functions (Arentoft et al, 2012;Arnold et al, 1994;Artiola i Fortuny et al, 1998;Coffey et al, 2005;Jeste et al, 2005;Luria, 1976;Saez et al, 2014;Vygotsky, 1962). The strong relevance of language can be seen even on tests that do not require a verbal response if one considers the receptive language skills needed to understand the task instructions or the use of internal language processing during task performance.…”
Section: Discussionsupporting
confidence: 56%
See 4 more Smart Citations
“…This finding is supported unambiguously by Coffey and colleagues' research, which demonstrated that more highly acculturated individuals, as measured by a language-based acculturation measure, exhibited better performance on the WCST total trials and non-perseverative errors relative to a those less acculturated (Coffey et al, 2005). Beyond this circumscribed finding, linguistic cultural factors have also been found to have a significant effect on an array of both verbal and nonverbal cognitive functions (Arentoft et al, 2012;Arnold et al, 1994;Artiola i Fortuny et al, 1998;Coffey et al, 2005;Jeste et al, 2005;Luria, 1976;Saez et al, 2014;Vygotsky, 1962). The strong relevance of language can be seen even on tests that do not require a verbal response if one considers the receptive language skills needed to understand the task instructions or the use of internal language processing during task performance.…”
Section: Discussionsupporting
confidence: 56%
“…Within the language domain, acculturation has been found to affect naming, repetition, fluency, and receptive and expressive vocabulary (Arnold & Orozco, 1989;Artiola i Fortuny et al, 1998;Manly, Jacobs, et al, 1998;Manly, Miller, et al, 1998) in some studies; however, other studies have found acculturation to be unrelated to some of the same measures (Boone et al, 2007;Kennepohl et al, 2004;Manly, Miller, et al, 1998;Touradji et al, 2001). Other positive and negative findings are similarly reported for attention, visuospatial functioning, processing speed, learning and memory, and perceptual and motor functioning (e.g., Arentoft et al, 2012;Boone et al, 2007;Kennepohl et al, 2004;Razani et al, 2007). Patterns embedded within this literature may become clearer with additional research.…”
Section: Introductionmentioning
confidence: 64%
See 3 more Smart Citations